2012
DOI: 10.1534/genetics.112.140483
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably Simple Sequence Requirement of the M-Factor Pheromone ofSchizosaccharomyces pombe

Abstract: The mating reaction is triggered by specific pheromones in a wide variety of organisms. Small peptides are used as mating pheromones in yeasts and fungi. In the fission yeast Schizosaccharomyces pombe, M-factor is a C terminally farnesylated nonapeptide secreted from M-cells, and its counterpart, P-factor, is a simple peptide composed of 23 amino acids. The primary structure requirements for the biological activity of pheromone peptides remain to be elucidated. Here, we conducted comprehensive substitution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Precursor proteins synthesized from these mfm genes are processed by as yet unidentified proteolytic enzymes to produce the same nonapeptide. Comprehensive mutagenesis has demonstrated that the primary sequence of the C-terminal half of M-factor is important for recognition by Map3 [17]. Both Mam2 and Map3 are heterotrimeric GTP-binding protein-coupled receptors containing 7 transmembrane domains.…”
Section: Introductionmentioning
confidence: 99%
“…Precursor proteins synthesized from these mfm genes are processed by as yet unidentified proteolytic enzymes to produce the same nonapeptide. Comprehensive mutagenesis has demonstrated that the primary sequence of the C-terminal half of M-factor is important for recognition by Map3 [17]. Both Mam2 and Map3 are heterotrimeric GTP-binding protein-coupled receptors containing 7 transmembrane domains.…”
Section: Introductionmentioning
confidence: 99%
“…(A) Strategy for creating a novel mating-type pair. The first step was the comprehensive amino acid substitution of mating pheromone M factor by in vitro site-directed mutagenesis as described previously (18). Among 152 single residue-substituted missense mutants, 35 sterile M-factor mutants were selected (shown in B).…”
Section: Resultsmentioning
confidence: 99%
“…If the modified pheromone (a ligand) and the receptor protein are structurally fit and ligand-induced activation of the receptor can be attained, the resulting modified versions of mating-competent cells might constitute a novel reproductive group. Owing to the small size of M factor (9 aa), a full set of single residue-substituted missense mutants of the mfm1 gene (coding for M factor) was previously successfully generated (18). Thorough screening of the 152 mfm1 mutants identified 35 sterile ones that might produce nonfunctional M-factor peptides.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations